The feasibility study of natural pigments as food colorants and seasonings pigments safety on dried tofu coloring - Wei-Sheng Lin; Pei Hua He; Chi-Fai Chau; Bo-Kang Liou; Shiming Li; Min-Hsiung Pan (Food Science and Human Wellness)
In order to improve appetite, attract consumers and even conform to the food culture, food coloring has become one of the necessary links in modern food processing. For example, dried-tofu will be colored by adding artificial food colors (AFCs) such as sunset yellow, cochineal red A or other seasonings like soy sauce. However, the dispute persists about whether AFCs are harmful to health. Some studies indicate AFCs affect children’s intelligence and attention, cause hyperactivity, and allergy when children consumed ≥ 50 mg. In addition, researches showed that chemical soy sauce produces a trace of methylglyoxal (MGO) in the manufacturing process, which is related to diseases such as oxidative stress, diabetes, and cognitive deterioration. Therefore, natural pigments are relatively new and promising strategy for replacing high-risk AFCs. Thus, the objective of this study was to use dried-tofu as a natural colorants coloring screening platform, through the concept of three primary colors to discuss the coloring effects of natural colorants in Taiwan in double –phase (liquid phase to solid phase) food coloring system and assess the effects of MGO on PC12 neuron cellular morphology and cell cycle at the dietary exposure in soy sauce. Our results showed that formula G：R = 0.2：0.8 and C：R = 0.08：0.92 were coloring by combined natural colorants had the same eye sensory quality acceptance of consumer and had the intention to purchase. Furthermore, the results from the PC12 cell suggested that dietary exposure of methylglyoxal (<50 μM) in soy sauce did not affect neuron cellular morphology and cell cycle significantly. Overall, Gardenia Yellow, Curcumin, and Radish Red could overcome the application restrictions in multiple-phase food coloring system and simultaneously soy sauce as a coloring agent was safety. It showed the possibility of them as food colorants on dried-tofu. Keywords: Natural colorants, Dried-tofu, The coloring from liquid phase system to solid phase system on dried-tofu